T6 Thrombocytosis is Associated with Increased Short and Long Term Mortality After Exacerbation of Chronic Obstructive Pulmonary Disease. (19th November 2012) - Harrison, MT; Short, P; Williamson, P; Singanayagam, A; Akram, AR; Chalmers, JD; Schembri, S
Abstract : Introduction: There is increasing evidence suggesting that platelets play a significant role in inflammation in addition to their established role in thrombosis. Systemic inflammation is linked to poor short and long term outcomes in COPD Increased platelet activation has been reported in acute exacerbations of COPD (AECOPD). We investigated whether thrombocytosis is associated with poor outcomes following AECOPD. Methods: A prospective observational cohort study of patients hospitalised with AECOPD was performed. The dataset consists of patients >40 years, with spirometrically confirmed COPD admitted with exacerbations between 2009–2011. Platelet count was recorded on admission. The primary outcome was in-hospital mortality with secondary outcomes of 1 year all-cause mortality, cardiovascular events and mortality. Analyses were conducted using cox-proportional hazards regression after adjustment for demographics, co-morbidities, chronic treatments and severity of exacerbations. Results: 1343 patients (49% male) were included with a median age of 72 years (interquartile range 63–79 years). 157 patients (11.7%) had thrombocytosis (platelet count >400×109 cells/mm3). Thrombocytosis correlated with established markers of poor outcome in COPD, including hypoalbuminaemia (34 IQR 31–38 vs 37 33–40, p<0.0001), low BMI (BMI <18.5 in 14.6% vs 9.1%, p=0.03) and frequent exacerbations in the previous year (mean 1.42 standard deviation(SD) 1.9 vs mean 1.1 SD 1.8, p=0.02). Thrombocytosis was significantly associated with in-hospital mortality: Hazard ratio (HR) 1.96 (1.15–3.32) and 1 year mortality after discharge HR 1.48 (1.12–1.97). The relationships with cardiovascular hospitalisation HR 1.17 (0.84–1.64) and 1 year cardiovascular mortality HR 1.33 (0.82–2.14) were not statistically significant. To determine if the increased risk associated with thrombocytosis was potentially modifiable, we studied whether antiplatelet treatment (chronic prescription of aspirin or clopidogrel) would attenuate the risks associated with thrombocytosis. Anti-platelet treatment was associated with reduced 1 year mortality HR 0.75 (0.59–0.97) with a trend towards reduced in-hospital mortality HR 0.66 (0.40–1.09), cardiovascular hospitalisation HR 0.81 (0.61–1.08) and cardiovascular death HR 0.85 (0.57–1.26). Conclusion: Thrombocytosis was associated with increased in-hospital and 1 year mortality. This relationship was only partly attributable to increased cardiovascular mortality. Anti-platelet medications correlated with significantly lower 1 year mortality and may have a protective role to play in COPD.